FORMATION OF VOLITIONAL QUALITIES IN HAND FIGHT ATHLETES (Proceedings of International Educators Conference, 2022)
Hand-to-hand combat as a type of martial art makes many specific requirements for the psyche of the hand-to-hand combatant, the presence of certain strong-willed qualities in him.